Financial inclusion and itâ€™s effect on poverty in Indonesia - Andrian, Thomas; Herlina Sitorus, Nurbetty; Febriana MK, Irma; Willy Chandra, Stefanus (Jurnal Paradigma Ekonomika, 2021)
This study aims to analyze and determine the impact of Financial Inclusion in Indonesia and other macroeconomic variables on poverty rate in Indonesia. This study uses secondary data. Analysis method with the Random Effect Model (REM) approach. The results of this study indicate that the variable Bank Service Offices per 1,000 km2 , Ratio of DPK, Ratio CRD have a negative and significant effect on poverty rate in 33 provinces in Indonesia in 2014-2018, and Unemployment Rate (UMP) has a positive and significant effect on poverty rate in 33 provinces in Indonesia in the 2014-2018 period. However, the variable Economic Growth and Inflation (INF) did not have a significant effect on poverty in 33 provinces in Indonesia in the 2014-2018 period. Measuring this dimension is still difficult to do and currently several international institutions were concerned about the development of financial inclusion. Â 